Præmiepløining ved Sorø, foranstaltet af Sorø Amts landoekonomiske Selskab. - Hald, J. C. (Tidsskrift for Landøkonomi, 2018)
Præmiepløining ved Sorø, foranstaltet af Sorø Amts landoekonomiske Selskab.